Beta-catenin signaling regulates barrier-specific gene expression in circumventricular organ and ocular vasculatures - Yanshu Wang; Mark F Sabbagh; Xiaowu Gu; Amir Rattner; John Williams; Jeremy Nathans (eLife, 2019)
The brain, spinal cord, and retina are supplied by capillaries that do not permit free diffusion of molecules between serum and parenchyma, a property that defines the blood-brain and blood-retina barriers. Exceptions to this pattern are found in circumventricular organs (CVOs), small midline brain structures that are supplied by high permeability capillaries. In the eye and brain, high permeability capillaries are also present in the choriocapillaris, which supplies the retinal pigment epithelium and photoreceptors, and the ciliary body and choroid plexus, the sources of aqueous humor and cerebrospinal fluid, respectively. We show here that (1) endothelial cells in these high permeability vascular systems have very low beta-catenin signaling compared to barrier-competent endothelial cells, and (2) elevating beta-catenin signaling leads to a partial conversion of permeable endothelial cells to a barrier-type state. In one CVO, the area postrema, high permeability is maintained, in part, by local production of Wnt inhibitory factor-1.